(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Cooperation is something worthy to be explored from a social, economic, biological and even genetic point of view. This paper deals with human cooperation and focuses specifically on how humans interact with intelligent machines, which are considered as entities that, along with others (humans and non-human animals), populate the same ecological niche. The discourse is based on two theoretical pillars: the hypothesis of self-domestication of humans and the niche construction theory. Then, the movement of intelligent machines from isolation to direct cooperation is shown as the factual technological change which raises the problem of how cooperation between humans and intelligent machines works and with what effects. A presentation of the two main visions about the future of human-machine relations is offered and the different possibilities of development of self-control between humans and intelligent machines are discussed. According to the Author, machines will not destroy humanity. Humans will co-evolve with the machines they create which they will control through social, ethical, and legal rules. In addition, humans, integrated with mechanical or electronic devices, will continue their evolution by developing their self-control as cyborgs. A final note is reserved for how our ecological niche is changing.